Children and the Sayings Source Q: What the Double Tradition Reveals about Q's Attitude toward Children (Q 11:19-20; 12:53; 14:26; and 17:1-2) - Murphy, A. James (Biblical interpretation, 2019)
This essay seeks to contribute to the growing scholarship on children in biblical studies, and while studies of children in the Gospels have begun to emerge, no one has examined the hypothetical Sayings Source Q material specifically with children in mind. Are there children in Q? What can we learn of Q's disposition toward children? This essay adapts K.S. Han's method of "allegiance types" (2002) for determining Q's attitude toward the Jerusalem Temple to a childist reading of Q 11:19-20; 12:53; 14:26; and 17:1-2. In short, these four passages evidence only adult or adolescent children, and despite much household imagery, Q language often suggests an "imperiled" family unit so central to the lives of children. The findings may aid studies seeking to further define Q's relationship to apocalypticism, "renewal" ideology, asceticism, or the endurance of the family unit.